The Effects of Designing a Transdisciplinary Inquiry-based Curriculum on Pre-service Teachers: A Case of International Baccalaureate - Gurkan, Burcu (TURKISH EDUCATION ASSOC, 2021)
The present study aims to investigate the effect of the design process of transdisciplinary inquiry curriculum on the PYP preservice teachers' group work skills, reflective thinking levels and curriculum design orientations. The study employs convergent design. For the quantitative part of the study a one-group pretest-posttest experimental design was employed, and the qualitative dimension was based on the case study design. The study group consisted of 15 pre-service teachers from different branches attending a university's International Baccalaureate Education Certificate training program. Pre- service teachers designed a transdisciplinary inquiry-based curriculum for 6 weeks. Qualitative data were collected through self-evaluation form, group evaluation form and semi-structured interview form. Quantitative data were collected through Group work Skills Scale, Reflective Thinking Levels Scale and Curriculum Design Orientations Scale. Qualitative data were analyzed through content analysis. Frequency analysis was performed for the evaluation forms; the results of the scales were analyzed with the Wilcoxon Signed-Rank Test. The effect size was calculated with the Pearson Correlation Coefficient (r) statistic. A significant difference was observed in the posttest in terms of the group work skills, reflective thinking levels, and curriculum design orientations of the preservice teachers in designing a transdisciplinary inquiry-based curriculum, which implies that the application was effective. The study found that pre-service teachers favored student-based and inquiry-based curriculum and their performances were improved in terms of fulfilling responsibilities, time-management, providing support and making an effort. In addition, pre-service teachers had difficulties in curriculum planning, writing main ideas, organizing activities, considering the age level and writing action etc.
Keywords: Transdisciplinary Inquiry-based; Curriculum; Group work Skills; Reflective Thinking Skills; Curriculum Design Orientations; International Baccalaureate